Exergetic Analysis in the Educational Field (Global Journal of Science Frontier Research, 2023)
The systematic review of the bibliographic heritage and other productions related to exergetic analysis highlights the growing use of this concept in the scientific community. We find this thermodynamic tool associated with other dimensions: the analysis of costs as an exergoeconomy, the environment as an exergo-ecology or as an emergy, the search for indicators that establish a universal metric on human activity and its relationship with the environment. environment, to the dispersion of mineral resources, to the production of renewable energies, also to the social dimension as social exergy. However, it remains ignored by society and even worse by those who have the responsibility to make decisions. This article humbly proposes to contribute to its dissemination in the educational field, inquiring about some strategies that allow its teaching in different realities.
Keywords: exergy; environment; education